Peningkatan Kesiapan Akreditasi Sekolah Melalui Workshop Pendampingan bagi Pendidik dan Tenaga Kependidikan di SMKN 1 Mentaya Hilir Selatan: Enhancing School Accreditation Readiness Through a Mentoring Workshop for Educators and Education Personnel at SMKN 1 Mentaya Hilir Selatan - Nurahman, Nurahman; Prasetyaningrum, Eka; Thaher, Muhammad Tarmizi; Budiyanto, Herwin (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
School readiness for the accreditation process is crucial in ensuring sustainable education quality. However, many schools still face challenges understanding accreditation instruments and systematically preparing supporting documents. SMKN 1 Mentaya Hilir Selatan, as a vocational high school undergoing accreditation, requires capacity strengthening for educators and education personnel in preparing for the various assessed aspects. To address this need, a community service program in the form of a mentoring workshop was conducted over three days, involving resource persons from academic and educational practitioner backgrounds. This activity was designed to be participatory and practical, covering the analysis of education report cards, preparation of school self-evaluation reports, and hands-on practice in compiling administrative accreditation documents. A total of 30 participants attended the workshop actively and enthusiastically. Evaluation results showed a significant increase in participants' understanding of accreditation instruments and their ability to prepare supporting documents. In addition, the activity fostered a collaborative work culture and awareness of quality within the school environment. This workshop served as a means of improving technical capacity and strengthening synergy between educators, school management, and external parties. The activity demonstrated that mentoring through workshops is an effective model for schools preparing for accreditation and can be replicated in other educational institutions with similar needs.